Comparative cytotoxicity, endocrine-disrupting effects, oxidative stress of halophenolic disinfection byproducts and the underlying molecular mechanisms revealed by transcriptome analysis. (1st February 2023) - Li, Xiuwen; Gao, Xinran; Li, Aimin; Xu, Shuhui; Zhou, Qing; Zhang, Lulu; Pan, Yang; Shi, Wei; Song, Maoyong; Shi, Peng
Highlights: Ranking and revealing the mechanism of the cytotoxicity of seven halophenolic DBPs. Anti-androgenic effects of halophenolic DBPs were proved. Halophenolic DBPs induce the oxidative stress to HepG2 cells. The MAPK signaling pathway plays a vital role in toxicity development. Abstract: Halophenolic disinfection byproducts (DBPs) are a class of emerging pollutants whose adverse effects on human cells and the underlying molecular mechanisms still need further exploration. In this study, we found that when halophenolic DBPs were substituted with the same halogen, the more substitution sites, the more cytotoxic, while when they were substituted at the same sites, the most toxic chemical was iodophenols, followed by bromophenols and chlorophenols. In addition, several of them exerted significant endocrine-disrupting effects at sublethal concentrations. 2, 4, 6-triiodophenol (TIP) and 2, 4-dichlorophenol (2, 4-DCP) showed the highest estradiol equivalent factor (EEF) of 4.41 × 10 −8 and flutamide equivalent factor (FEF) of 0.4, respectively. Furthermore, all of the halophenolic DBPs except for 2-chlorophenol (2-CP) and 2-bromophenol (2-BP) significantly increased the levels of reactive oxygen species (ROS) or 8-hydroxydeoxyguanosine (8-OHdG) in HepG2 cells. The lowest cytotoxicity and unchanged ROS and 8-OHdG levels after 2-CP exposure may result from the activation of the transporters of the adenosine triphosphate (ATP) binding cassette in cells. Transcriptome analysis revealed distinct grouping patterns of 2-CP, 2, 6-dibromophenol (2, 6-DBP), and TIP at the concentrations of EC20, and the top differentially expressed genes (DEGs) were involved in the antioxidant-, immune-, and endocrine-associated systems. The weighted gene correlation network analysis well connected the phenotypes (EC50, EEF, FEF, ROS, 8-OHdG, and ABC transporters) with the DEGs and revealed that the MAPK signaling pathway played a vital role in regulating the biological response after exposure to halophenolic DBPs. This study provides deep insights into the underlying mechanisms of the toxic effects induced by halophenolic DBPs. Graphical abstract: Image, graphical abstract